Adhesive structure
Patent Information
- Application Number
- JP2023149147
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
Smart Images

Figure 2025042252000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive structure. [Background technology]
[0002] For example, in semiconductor manufacturing equipment, if particles or the like are present on the holding surface of a semiconductor wafer, the flatness of the holding surface is impaired, causing manufacturing defects and reducing yields. Conventionally, as a method for removing particles, for example, as shown in Patent Document 1, a substrate to which an adhesive substance is adhered is used as a cleaning wafer, and this cleaning wafer is transported empty to remove particles in the transport system and processing unit.
[0003] In addition, in the case of a gripping member that grips an object and a transport member that transports an object, as shown in Patent Documents 2 and 3, for example, an adhesive structure having adhesive properties is arranged in the portion that comes into contact with the object in order to stably fix the object. Furthermore, when handling an object, for example, as shown in Patent Document 4, an adhesive structure having adhesiveness is used to temporarily fix the object and prevent it from shifting position. Here, since the bonded structure is required to have a sufficient frictional force between itself and the object, it is usually made of an organic material such as rubber, which is a viscoelastic body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-117440 A [Patent Document 2] JP 2018-094704 A [Patent Document 3] WO2009 / 005027 publication [Patent Document 4] JP 2009-168860 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the method disclosed in Patent Document 1, it is necessary to temporarily stop the operation of the semiconductor manufacturing equipment or to lower the environmental temperature to 400° C. or lower when removing particles, and the downtime causes a problem of reduced productivity. In addition, organic materials such as rubber have problems in that they cannot be used stably in high-temperature environments due to insufficient heat resistance, and they cannot be used in clean environments due to the risk of contamination by the organic materials. Therefore, for example, bonded structures made of organic materials could not be applied to semiconductor manufacturing process applications, aerospace applications, and robot applications.
[0006] Here, the industrial materials constituting the various members are roughly divided into organic materials such as resin and rubber, and inorganic materials such as ceramics and metals. As mentioned above, organic materials have excellent flexibility but poor heat resistance. In contrast, inorganic materials have excellent heat resistance but poor flexibility. Thus, when it comes to industrial materials, a trade-off in properties occurs depending on the material selected.
[0007] For this reason, when the adhesive structure is made of an inorganic material, it has excellent heat resistance and reduces contamination problems, but there is a risk that it is not possible to obtain sufficient adhesive strength, and it is not possible to adequately fix the object or to adsorb and remove particles.
[0008] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide an adhesive structure that can be used stably even in high-temperature environments and clean environments and that can obtain sufficient adhesive strength. [Means for solving the problem]
[0009] In order to solve this problem, the inventors conducted extensive research and discovered that by forming a special structure on the surface of a substrate made of an inorganic material such as ceramics or metal, sufficient adhesive strength can be imparted to the surface, making it possible to use the substrate as an adhesive structure.
[0010] The present invention has been made based on the above-mentioned findings, and the adhesive structure of embodiment 1 of the present invention is characterized in that a tube array structure in which a plurality of tube bodies made of a metal oxide are arranged upright on at least a portion of the surface of a substrate made of an inorganic material is formed.
[0011] According to the bonded structure of the first aspect of the present invention, since it is made of inorganic materials such as ceramics and metals, it has excellent heat resistance and can sufficiently suppress the problem of contamination. Furthermore, since a tube array structure in which a plurality of tube bodies made of metal oxide are erected is formed on at least a part of the surface of the substrate, it is possible to impart sufficient adhesive strength to the surface of the substrate. Therefore, it can be used stably even in high-temperature and clean environments, and sufficient adhesive strength can be obtained. That is, the bonded structure of the first aspect of the present invention can be used as an anti-slip member or a foreign matter adsorbing member that can be used stably even in high-temperature and clean environments.
[0012] A second aspect of the present invention is characterized in that in the bonded structure of the first aspect, the metal oxide is aluminum oxide or titanium oxide. According to the adhesive structure of aspect 2 of the present invention, the tube bodies constituting the tube array structure are made of aluminum oxide or titanium oxide, so that sufficient adhesive strength can be obtained, the heat resistance is excellent, and the problem of contamination can be sufficiently suppressed.
[0013] A third aspect of the present invention is the bonded structure of the first or second aspect, characterized in that the tube body has an average outer diameter D of 40 nm or more and an average height H of 300 nm or more. According to the adhesive structure of aspect 3 of the present invention, the average outer diameter D of the tube body is 40 nm or more and the average height H is 300 nm or more, so that the tube array structure formed from this tube body can reliably obtain sufficient adhesive strength.
[0014] A fourth aspect of the present invention is the bonded structure according to any one of the first to third aspects, characterized in that the average inner diameter of the tube body is 10 nm or more. According to the adhesive structure of the fourth aspect of the present invention, the average inner diameter of the tube bodies is set to 10 nm or more, so that a tube array structure constituted by these tube bodies can reliably obtain sufficient adhesive strength.
[0015] A fifth aspect of the present invention is characterized in that, in the adhesive structure of any one of the first to fourth aspects, the aspect ratio H / D calculated from the average outer diameter D and average height H of the tube body is 3 or more and 30 or less. According to the adhesive structure of aspect 5 of the present invention, the aspect ratio H / D calculated from the average outer diameter D and average height H of the tube body is 3 or more and 30 or less, so that a tube array structure formed from this tube body can reliably obtain sufficient adhesive strength.
[0016] A sixth aspect of the present invention is characterized in that in the bonded structure of any one of the first to fifth aspects, the occupancy rate of the surface of the tube array structure is 30% or more. According to the bonded structure of aspect 6 of the present invention, the occupancy rate of the surface of the tube array structure is 30% or more, so that sufficient adhesive strength can be reliably obtained.
[0017] A seventh aspect of the present invention is characterized in that in the bonded structure of any one of the first to sixth aspects, the surface of the substrate has a static friction coefficient against silicon of 0.30 or more. According to the bonded structure of the seventh aspect of the present invention, the static friction coefficient of the surface of the base material against silicon is set to 0.30 or more, so that the target member can be reliably fixed.
[0018] An eighth aspect of the present invention is characterized in that in the bonded structure of any one of the first to seventh aspects, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more. According to the bonded structure of embodiment 8 of the present invention, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more, so that the particles can be reliably adhered and removed. Effect of the Invention
[0019] According to the present invention, it is possible to provide an adhesive structure that can be stably used even in high temperature and clean environments and that can obtain sufficient adhesive strength. [Brief description of the drawings]
[0020] [Figure 1] 1 is a schematic explanatory diagram of an adhesive structure according to an embodiment of the present invention; [Diagram 2] 1 is an observation photograph of a tube array structure in a bonded structure according to one embodiment of the present invention. [Diagram 3] FIG. [Figure 4] FIG. 2 is an explanatory diagram showing a method for measuring a static friction coefficient. [Diagram 5] FIG. 2 is an explanatory diagram showing a method for measuring a particle adsorption rate. [Figure 6] FIG. 2 is a flow diagram showing a method for manufacturing a bonded structure according to the present embodiment. [Figure 7] FIG. 2 is an explanatory diagram showing a method for measuring the static friction coefficient in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an adhesive structure 10 according to one embodiment of the present invention will be described with reference to the accompanying drawings. The adhesive structure 10 of this embodiment is used, for example, in gripping devices, conveying devices, manufacturing devices, etc. that are used in high temperature or clean environments in the aerospace field, semiconductor manufacturing process field, medical field, etc., to temporarily fix objects or adsorb and remove particles present on the surface of a substrate, etc.
[0022] The adhesive structure 10 of this embodiment has a substrate 11 made of an inorganic material such as ceramics or metal, and a tube array structure 20 having a plurality of tube bodies 21 made of a metal oxide arranged upright on at least a portion of the surface of the substrate 11 is formed. There is no particular restriction on the shape or size of the base material 11, but in this embodiment, as shown in FIG. 1, it is in the form of a plate, and its thickness is within the range of, for example, 10 μm or more and 10 cm or less.
[0023] Here, examples of inorganic materials constituting the base material 11 include metals, ceramics, silicon, and glass. The inorganic material constituting the base material 11 preferably has a melting point of 100° C. or higher and a decomposition temperature of 100° C. or higher, more preferably has a melting point of 300° C. or higher and a decomposition temperature of 300° C. or higher, and even more preferably has a melting point of 500° C. or higher and a decomposition temperature of 500° C. or higher.
[0024] The metal constituting the substrate 11 may be a simple metal or an alloy. Alloys include those made of a plurality of metal elements and those made of a metal element and a nonmetal element. Examples of simple metals include aluminum, nickel, iron, copper, titanium, tungsten, and magnesium. Examples of alloys include aluminum alloys, NiP, stainless steel, and copper alloys. Oxides, nitrides, and carbides can be used as the ceramics constituting the base material 11. Examples of ceramics include aluminum oxide (alumina), titanium oxide, and quartz. The inorganic material constituting the substrate 11 is preferably a metal, and more preferably contains any of copper, a copper alloy, aluminum, an aluminum alloy, and a NiP alloy.
[0025] The tube array structure 20 formed on the surface of the substrate 11 has a structure in which a plurality of tube bodies 21 made of metal oxide are arranged upright, as shown in FIGS. Here, the metal oxide constituting the tube body 21 is preferably, for example, aluminum oxide or titanium oxide. In this embodiment, the base material 11 is made of titanium, and the tube body 21 is made of titanium oxide.
[0026] Here, it is preferable that the tube body 21 has an average height of 300 nm or more. The height of the tube body 21 can be measured from a cross-sectional SEM photograph of the tube array structure 20 taken with a SEM (scanning electron microscope). The average height H of the tube body 21 is preferably 400 nm or more, and more preferably 500 nm or more, while the average height H of the tube body 21 is preferably 5000 nm or less, and more preferably 3000 nm or less.
[0027] The tube body 21 preferably has an average outer diameter D of 40 nm or more. The outer diameter of the tube body 21 can be measured from a cross-sectional SEM photograph of the tube array structure 20 taken with a SEM (scanning electron microscope). The lower limit of the average outer diameter D of the tube body 21 is preferably 50 nm or more, and more preferably 70 nm or more. On the other hand, the average outer diameter D of the tube body 21 is preferably 700 nm or less, and more preferably 500 nm or less.
[0028] The tube body 21 preferably has an average inner diameter d of 10 nm or more. The inner diameter of the tube body 21 can be measured from a cross-sectional SEM photograph of the tube array structure 20 taken with a SEM (scanning electron microscope). The average inner diameter d of the tube body 21 is preferably 12 nm or more, and more preferably 14 nm or more, while the average inner diameter d of the tube body 21 is preferably 500 nm or less, and more preferably 300 nm or less.
[0029] Moreover, it is preferable that the aspect ratio H / D of the tube body 21, calculated from the average outer diameter D and average height H of the tube body 21, is within a range of 3 to 30. The aspect ratio of the tube body 21 can be measured from a cross-sectional SEM photograph of the tube array structure 20 taken with a SEM (scanning electron microscope). The aspect ratio H / D of the tube body 21 is preferably 4 or more, and more preferably 5 or more. On the other hand, the aspect ratio H / D of the tube body 21 is preferably 25 or less, and more preferably 20 or less.
[0030] In the bonded structure 10 of this embodiment, the area ratio (occupancy rate) of the surface (bonded surface) occupied by the tube array structure 20 is preferably 30% or more. In the bonded structure 10 shown in FIG. 1, the tube array structure 20 is formed on approximately 70% of the surface of the substrate 11 . The area ratio of the tube array structure 20 to the surface of the base material 11 is preferably 50% or more, more preferably 70% or more, and is 100% or less.
[0031] In the bonded structure 10 of this embodiment, the static friction coefficient μ of the surface of the base material 11 on which the tube array structure 20 is formed is set to 0.30 or more. The static friction coefficient μ on the surface of the substrate 11 is preferably 0.35 or more, and more preferably 0.40 or more. There is no particular upper limit to the static friction coefficient μ, but in reality, the static friction coefficient μ is 10 or less. Here, the static friction coefficient μ on the surface of the substrate 11 can be calculated by the formula shown in Fig. 4. In Fig. 4, m is the mass of the object, g is the gravitational acceleration, F0 is the maximum static friction force, and N is the normal force. Specifically, when the angle at which sliding begins is θ, the static friction coefficient μ is expressed as μ=tan θ.
[0032] In addition, in the bonded structure 10 of this embodiment, the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is set to 5% or more. Here, the particle adsorption rate can be calculated by the procedure shown in Figure 5. That is, a liquid containing particles with a particle diameter of 1 μm to 30 μm (PSL particles: polystyrene latex particles) is dropped onto the surface of the object to disperse the particles. The surface of the adhesive structure on which the tube array structure is formed is brought into contact with the object to adsorb the particles. The number of particles in the contact area of the bonded structure on the surface of the object before and after contact with the bonded structure is counted, and the particle adsorption rate is calculated.
[0033] Next, a description will be given of an example of a method for manufacturing the bonded structure 10 of this embodiment. In the bonded structure 10 of this embodiment, as described above, the base material 11 is made of titanium, and the tube body 21 is made of titanium oxide. As shown in the flow diagram of FIG. 6, this embodiment includes a chemical polishing step S01 and an anodizing step S02.
[0034] In the chemical polishing step S01, the surface of the base material 11 made of an inorganic material (titanium) is chemically polished to smooth the surface. The substrate 11 is immersed in a chemical polishing solution suited to the material thereof, and chemical polishing is performed under conditions of a temperature of 20° C. to 50° C. and a retention time of 1 minute to 10 minutes.
[0035] In the anodization step S02, the surface of the base material 11 polished in the chemical polishing step S01 is anodized. By the anodization, a porous structure is formed in the surface of the base material 11, and the walls are separated and independent to form a tube array structure 20 in which a plurality of tube bodies 21 are erected.
[0036] The treatment liquid used in the anodization may be, for example, a mixture of an aqueous solution of ammonium fluoride and an aqueous solution of ethylene glycol. Then, anodization is carried out under conditions of a voltage of 5 V or more and 100 V or less, a temperature of 10° C. or more and 30° C. or less, and a holding time of 5 minutes or more and 60 minutes or less.
[0037] The bonded structure 10 of this embodiment is manufactured by the above-mentioned steps.
[0038] The bonded structure 10 of this embodiment configured as described above is made of inorganic materials such as ceramics and metals, and therefore has excellent heat resistance and can sufficiently suppress the problem of contamination. Furthermore, the tube array structure 20 in which a plurality of tube bodies 21 made of metal oxide are erected is formed on at least a part of the surface of the base material 11, so that it is possible to impart sufficient adhesive strength to the surface of the base material 11. Therefore, the adhesive can be stably used even in high temperature and clean environments, and sufficient adhesive strength can be obtained.
[0039] In the adhesive structure 10 of this embodiment, when the metal oxide constituting the tube body 21 is composed of aluminum oxide or titanium oxide, an appropriate tube array structure 20 can be formed to obtain sufficient adhesive strength.
[0040] In the adhesive structure 10 of this embodiment, when the tube bodies 21 constituting the tube array structure 20 have an average outer diameter of 40 nm or more and an average height of 300 nm or more, the tube array structure 20 composed of these tube bodies 21 can reliably obtain sufficient adhesive strength.
[0041] In the bonded structure 10 of this embodiment, when the average inner diameter of the tube bodies 21 is 10 nm or more, the tube array structure 20 constituted by these tube bodies 21 can reliably obtain a sufficient adhesive strength.
[0042] In the adhesive structure 10 of this embodiment, when the aspect ratio H / D calculated from the average outer diameter D and average height H of the tube body 21 is 3 or more and 30 or less, a sufficient adhesive strength can be reliably obtained by the tube array structure formed by this tube body 21.
[0043] In the bonded structure 10 of this embodiment, when the area ratio of the tube array structure 20 on the surface of the base material 11 is 30% or more, the tube array structure 20 can reliably obtain a sufficient adhesive strength.
[0044] In the bonded structure 10 of this embodiment, if the static friction coefficient of the surface of the base material 11 against silicon is 0.30 or more, the bonded structure 10 can be used to reliably fix a target member.
[0045] In the bonded structure 10 of this embodiment, when the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more, particles present on the surface of an object can be reliably adhered and removed.
[0046] Although the bonded structure according to the embodiment of the present invention has been described above, the present invention is not limited thereto, and can be modified as appropriate without departing from the technical concept of the invention. For example, in this embodiment, the substrate is described as being titanium, and the tube bodies constituting the tube array structure are formed from titanium oxide, but this is not limited to this, and the substrate may be made of other inorganic materials, and the tube bodies may be made of other metal oxides such as aluminum oxide. EXAMPLES
[0047] The results of experiments carried out to confirm the effects of the present invention will be described below.
[0048] First, a substrate (length: 7 mm, width: 7 mm, thickness: 1 mm) made of an inorganic material shown in Table 1 was prepared. The prepared substrate was chemically polished using a chemical polishing solution (TCP-80 manufactured by Mitsubishi Gas Chemical Co., Inc.) at 30° C. for 5 minutes. The chemically polished sample was anodized by constant voltage electrolysis for 20 minutes in an ethylene glycol aqueous solution containing 0.38 mass% NH4F and 10 mass% HO at a bath temperature of 20°C under the voltage conditions shown in Table 1. This produced an adhesive structure with a tube array structure. The average inner diameter, average outer diameter, average height, and aspect ratio H / D of the tube bodies constituting the tube array structure are as shown in Table 1.
[0049] (Static friction coefficient) The static friction coefficient of the surface of the resulting bonded structure on which the tube array structure was formed was measured. A 300 mm disk-shaped silicon wafer S was prepared. The surface roughness Ra of the silicon wafer S was set to 0.14 nm. As shown in FIG. 7, four bonded structures 10 were arranged at 90° intervals in the circumferential direction at a radial position 140 mm from the center of the silicon wafer S, and placed on a fixed plate Q.
[0050] The adhesive structure 10 was placed so that the surface on which the tube array structure was formed faced the silicon wafer S. In addition, by using a silicon wafer with a mass of 128 g, the load in the stacking direction was 43 g / cm 2 It was decided. The fixed plate Q was then tilted, the angle θ at which the silicon wafer S slid down was measured, and the static friction coefficient was calculated. The results are shown in Table 1.
[0051] (Particle adsorption rate) A 300 mm disk-shaped silicon wafer S was prepared. A liquid containing standard particles with an average particle diameter of 30 μm was dropped onto the surface of the silicon wafer to disperse the standard particles. In this state, the number of particles present in the area where the adhesive structure was to be laminated on the surface of the silicon wafer was measured using a particle counter. Next, the adhesive structure and the silicon wafer were stacked so that the surface of the above-mentioned adhesive structure on which the tube array structure was formed was in contact with the surface of the silicon wafer S on which standard particles (polystyrene latex particles: 30 μm) were dispersed, and after keeping them in contact for 30 seconds, the adhesive structure was removed.
[0052] The number of particles present on the surface of the silicon wafer in the area where the adhesive structure was laminated was measured using a particle counter. The particle adsorption rate was calculated from the number of particles before and after laminating the adhesive structure. The results are shown in Table 1.
[0053] [Table 1]
[0054] In Comparative Examples 1 and 2, the tube array structure was not formed, the static friction coefficient was low at 0.23, and the surface friction force was insufficient, making it difficult to firmly fix the target object. In addition, the particle adsorption rate was 0.0%, and no effect of removing particles was observed.
[0055] In contrast, in Examples 1 to 8 of the present invention, a tube array structure was formed, and it was confirmed that the static friction coefficient of the surface was 0.30 or more, and the frictional force was high enough to sufficiently fix the object. It was also confirmed that the particle adsorption rate was 5% or more, making it possible to remove particles present on the surface of the target object.
[0056] From the above, it was confirmed that the present invention can provide an adhesive structure that can be stably used even in high temperature and clean environments and that can obtain sufficient adhesive strength. [Explanation of symbols]
[0057] 10 Adhesive structure 11 Base material 20 Tube array structure 21 Tube body
Claims
1. An adhesive structure, comprising a substrate made of an inorganic material and a tube array structure having a plurality of tube bodies made of a metal oxide arranged upright on at least a portion of the surface of the substrate.
2. 2. The bonded structure according to claim 1, wherein the metal oxide is aluminum oxide or titanium oxide.
3. 3. The bonded structure according to claim 1, wherein the tube body has an average outer diameter D of 40 nm or more and an average height H of 300 nm or more.
4. 3. The bonded structure according to claim 1, wherein the tube body has an average inner diameter of 10 nm or more.
5. 3. The bonded structure according to claim 1, wherein an aspect ratio H / D calculated from the average outer diameter D and the average height H of the tube body is 3 or more and 30 or less.
6. 3. The adhesive structure according to claim 1, wherein the occupancy rate of the surface of the tube array structure is 30% or more.
7. 3. The bonded structure according to claim 1, wherein the surface of the substrate has a static friction coefficient with respect to silicon of 0.30 or more.
8. 3. The bonded structure according to claim 1, wherein the adsorption rate of particles having a particle diameter of 1 μm or more and 30 μm or less is 5% or more.
Citation Information
Patent Citations
Cleaning wafer
JP2009117440A
Stage device for substrate
JP2009168860A
Gripper to be mounted on robot
JP2018094704A
Substrate transfer robot and vacuum processing apparatus provided with the same
WO2009005027A1